Facing Reality - Eccles, J. C. author. aut Link
XI, 210 p.
Keywords: The titling of this book - "Facing Reality" - came to me unbidden, presumably from my subconscious! But, when it came, it seemed to be right, because that essentially is what I am trying to do in this book. " Facing" is to be understood in the sense of "looking at in a steadfast and unflinching manner". It thus contrasts with "Confronting" which has the sense of "looking at with hostility and defiance". As I face life with its joys and its sorrows, its successes and its failures, its peace and its turmoil, my attitude is one of serene acceptance and gratitude and not one of angry and arrogant confrontation and rejection. The other component of the title - "Reality" - is the ultimate reality for each of us as conscious beings - our birth - our self-hood in its long stream of becoming throughout our life - our death and apparent annihilation. This is the Reality that we each of us must face if we are to live and adventure as free and responsible beings and not as mere playthings of chance and circumstance, going through a mean ingless farce from birth to death with the search ever for distraction and self-forgetfulness. As a brain scientist I have specialist knowledge of that wonderful part of the body that is alone concerned in the whole Iife-Iong interplay between the conscious self and the extern al world, including other selves.